Pengaruh Kapabilitas APIP dan Dukungan Manajemen terhadap Efektivitas Peran Audit Internal serta Implikasinya terhadap Kualitas Laporan Keuangan Pemerintah Daerah - Sri Dewi Widjaya (Sekolah Pascasarjana Perbanas Jakarta, 2022)
One of the causes of fraud in the area is due to weak supervision. The supervisory system consists of internal supervision, namely supervision by the apparatus through inherent supervision, functional supervision, and external supervision carried out by the public and a constitutional supervisory agency, namely the Supreme Audit Agency (BPK). Based on data from the Audit Results Index of the Supreme Audit Agency (BPK), in 2016 to 2019 the quality of the preparation of Local Government Financial Reports in Indonesia, there was an increase in the number of BPK findings in 2017 on the weaknesses of the SPI and non-compliance with statutory provisions.The result of an effective internal audit role is to produce qualified financial reporting, transparent and accountable. The purpose of this study is to empirically study: (1) The effect of capability of internal auditor, and management support on internal auditor role effectiveness; (2) The effect of internaauditor role effectiveness on local government financial reporting quality. This bresearch uses survey method with description verification approach and type of causal research, conducted on 40 respondent from Inspectorat of Local Government in West Java Island. The type of data is primary data collected by a questionnaire research instruments. The data were analyzed by Statistikal Package for the Social Sciens (SPSS). The result of this study finds that the internal auditor capability not affect the internal auditor role effectiveness and financial reporting quality , but the management support did. The internal auditor role effectiveness in mediating with pseudo the positive affect of management support on financial reporting quality. The internal auditor role effectiveness affect the financial reporting quality without mediating through the internal auditor role effectiveness. The local government should give support, make policy to enhance the internal auditor capability and enhance the internal audit role in order to produce qualified financial reporting.